Preparation method of water-soluble carbon dot-based afterglow luminescent material and water-soluble carbon dot-based afterglow luminescent material
By reacting NaReF4 and carbon dots under a high temperature nitrogen atmosphere to generate nano-scale CDs@NaReF4 nanoparticles and performing pickling treatment, the problems of unstability and agglomeration of existing water-soluble carbon dot-based afterglow luminescent materials are solved, and nano-scale, acid-resistant water-soluble carbon dot-based afterglow luminescent materials are realized, and their application fields are expanded.
Patent Information
- Application Number
- CN202411702928.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing water-soluble carbon dot-based afterglow luminescent materials are unstable in solution environments, prone to agglomeration and dissolution, especially in strong acid environments to lose their afterglow luminescent properties.
Through a preparation method, NaReF4 is used as a matrix to generate carbon dots simultaneously, and react under a high-temperature nitrogen atmosphere, so that the carbon dots are embedded in NaReF4 in situ to form nanoscale CDs@NaReF4 nanoparticles, and hydrophobic groups are removed by acid washing to obtain a water-soluble hydr-CDs@NaReF4 composite material.
It has realized a water-soluble carbon dot-based afterglow luminescent material that is nano-scale, strong acid-resistant, and is not easy to accumulate in solution environments, expanding its application potential in harsh environments.
Smart Images

Figure CN119799329A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of luminescent carbon nanomaterials, in particular to the technical field of fluorescent carbon dots (CDs) preparation, and specifically to a preparation method of a water-soluble carbon dot-based afterglow luminescent material and a water-soluble carbon dot-based afterglow luminescent material. Background Art
[0002] In recent years, non-metal-doped solid-state room-temperature afterglow carbon dots have attracted extensive attention due to their simple preparation, low toxicity, excellent optical properties, and easy surface modification. However, the intersystem crossing (ISC) process associated with their room-temperature afterglow emission is usually affected by molecular vibration / rotation and surrounding dissolved oxygen, resulting in afterglow quenching, which greatly hinders their application. At present, carbon dot-based afterglow luminescent materials still cannot stabilize the triplet state of carbon dots in a solution environment, resulting in a short afterglow luminescence lifetime. In practical applications, the smaller the size of the carbon dot-based afterglow luminescent material, the less likely it is to deposit, which can better improve the stability of the carbon dot-based afterglow luminescent material in a solution environment. In this regard, the prior art has adopted SiO 2 The nanoscale carbon dot-based afterglow luminescent material obtained by coating method, namely, hyd-CDs@SiO 2 Composite materials.
[0003] Although CDs@SiO 2 Composite materials reach nanoscale, but still have shortcomings: CDs@SiO 2 The composite material is mainly prepared by the sol-gel method. It has a large number of silanol groups on its surface, which are easy to agglomerate, so that it is easy to aggregate in aqueous solution for a long time, and finally leads to CDs@SiO 2 The composite material is large in size in aqueous solution, and it is also not possible to achieve the problem of small particle size and not prone to sedimentation and aggregation. 2 The matrix of the composite material is SiO 2 When the solution environment is a strong acid environment, CDs@SiO 2 SiO in composite materials 2 It is easy to react with strong acid solution, resulting in CDs@SiO 2 The composite material dissolves and loses its afterglow luminescence performance. Therefore, it is urgent to improve the nano-scale water-soluble carbon dot-based afterglow luminescence material to expand the application field of the water-soluble carbon dot-based afterglow luminescence material. Summary of the invention
[0004] One of the purposes of the present invention is to avoid the shortcomings of the prior art and provide a method for preparing a water-soluble carbon dot-based afterglow luminescent material. The preparation method can prepare a nano-scale, strong acid-resistant, and non-aggregate-resistant water-soluble carbon dot-based afterglow luminescent material in a solution environment. The method has the advantages of easy operation and low cost.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] Provided is a method for preparing a water-soluble carbon dot-based afterglow luminescent material, comprising the following steps:
[0007] S1, add Re(CH 3 CO 2 ) 3 The solution, oleic acid and 1-octadecene are mixed uniformly to obtain a first mixed solution.
[0008] S2, stirring the first mixed solution and heating it to 140° C. to 170° C., reacting for 30 min to 50 min;
[0009] S3, adding citrate to the first mixed solution, mixing evenly to obtain a second mixed solution, and continuing to heat the second mixed solution at 140° C. to 170° C. for 8 min to 11 min, and then cooling to room temperature;
[0010] S4, adding NaOH methanol solution and NH4F methanol solution to the second mixed solution at room temperature, heating the second mixed solution to 40° C. to 60° C., and reacting for 25 min to 40 min to obtain a third mixed solution;
[0011] S5, heating the third mixed solution to 90° C. to 110° C., evacuating the solution, then heating the third mixed solution to 280° C. to 320° C., reacting the solution under a nitrogen atmosphere for 1 h to 3 h, and naturally cooling the third mixed solution to room temperature;
[0012] S6, adding the ethanol solution and the cyclohexane solution to the third mixed solution, mixing them evenly to obtain a fourth mixed solution, and then centrifuging the fourth mixed solution to obtain precipitated CDs@NaReF 4 Nanoparticles, using a mixed solution of ethanol solution and cyclohexane solution to precipitate CDs@NaReF 4 The nanoparticles are washed;
[0013] S7, then clean the CDs@NaReF with ethanol solution 4 Nanoparticles, then hydrochloric acid solution CDs@NaReF 4 Nanoparticles for acid washing to remove CDs@NaReF 4 The hydrophobic groups of the nanoparticles give water-soluble hyd-CDs@NaReF 4 Composite materials.
[0014] In some embodiments, in S1, per mole of Re(CH 3 CO2 ) 3 Add 5ml-8ml of oleic acid and 15ml-20ml of 1-octadecene to the solution.
[0015] In some embodiments, in S2, a galvanic temperature sensor is added to the first mixed solution, and stirring is performed using a stirring magnet.
[0016] In some embodiments, in S3, per mole of Re(CH 3 CO 2 ) 3 Add 50mg to 100mg of citrate to the solution.
[0017] In some embodiments, in S4, per mole of Re(CH 3 CO 2 ) 3 Add 1.5 mmol to 3 mmol of NaOH methanol solution and 2 mmol to 5 mmol of NH 4 F methanol solution.
[0018] In some embodiments, in S5, the vacuum treatment step includes: using a vacuum pump, connecting the vacuum pump to a double-row tube, and inserting the double-row tube into the third mixed solution for degassing for 8 minutes to 12 minutes.
[0019] In some embodiments, in S6, per mole of Re(CH 3 CO 2 ) 3 The solution is added with 15ml-25ml of ethanol solution and 5ml-15ml of cyclohexane solution.
[0020] In some embodiments, in S7, per mole of Re(CH 3 CO 2 ) 3 The solution was washed with 10 ml to 25 ml of ethanol solution. 3 CO 2 ) 3 The solution is cleaned with 4ml to 8ml of hydrochloric acid solution.
[0021] In some embodiments, the concentration of the hydrochloric acid solution is 1 mol / L to 2 mol / L, and the number of acid washings is 2 to 3.
[0022] The beneficial effects of the preparation method of a water-soluble carbon dot-based afterglow luminescent material of the present invention are as follows:
[0023] (1) The water-soluble carbon dot-based afterglow luminescent material of the present invention, the method makes NaReF 4 The matrix and carbon dots are generated simultaneously and the carbon dots are embedded in NaReF in situ.4 In the matrix, a new material CDs@NaReF with a small nano-sized surface and oleic acid ligands was first obtained. 4 Nanoparticles, and finally the new material CDs@NaReF is removed by acid washing 4 Nanoparticles capped with oleic acid ligands to obtain hydrophilic CDs@NaReF 4 Composite material, labeled as hyd-CDs@NaReF 4 Nanoparticles, hyd-CDs@NaReF 4 The composite material has no hydrophobic groups on its surface, is water-soluble, and can be evenly dispersed in a solution environment without agglomeration.
[0024] (2) The water-soluble carbon dot-based afterglow luminescent material of the present invention, hyd-CDs@NaReF 4 Nanoparticles based on NaReF 4 The size of hyd-CDs@NaReF can be realized at the nanoscale, and due to 4 There is no ligand on the surface and NaReF is used 4 Rare earth fluorides as rigid matrix of carbon dots overcome the traditional CDs@SiO 2 The composite material has no problems of single matrix type and serious agglomeration, and will not aggregate, and can be well dispersed in aqueous solution.
[0025] (3) The water-soluble carbon dot-based afterglow luminescent material of the present invention, hyd-CDs@NaReF 4 NaReF in Nanoparticles 4 It is an acid-resistant matrix and can be well dispersed in strong acid solutions, which expands the NaReF 4 Application scenarios of nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The hyd-CDs@NaYF synthesized in Experimental Example 1 4 Transmission electron microscopy image of the composite material.
[0027] Figure 2 The hyd-CDs@NaYF synthesized in Experimental Example 1 4 X-ray diffraction patterns of the composite materials.
[0028] Figure 3 The hyd-CDs@NaYF synthesized in Experimental Example 1 4 Fluorescence emission spectrum, afterglow excitation / emission spectrum and afterglow lifetime decay curve measured after the composite material was dispersed in aqueous solution.
[0029] Figure 4 The hyd-CDs@NaYF synthesized in Experimental Example 1 4Photographs of the composite material dispersed in aqueous solution, concentrated hydrochloric acid and concentrated nitric acid and treated with ultrasound for 30 min with the fluorescent lamp and 365 nm UV lamp turned on and off. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the preferred embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0031] The terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms of "a", "the" and "the" used in the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0032] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0033] Example 1
[0034] The method for preparing the water-soluble carbon dot-based afterglow luminescent material disclosed in this embodiment comprises the following steps:
[0035] S1. Add Re(CH 3 CO 2 ) 3 The solution, oleic acid and 1-octadecene are mixed uniformly to obtain a first mixed solution.
[0036] In the above steps, Re(CH 3 CO 2 ) 3 Solution as matrix, Re(CH 3 CO 2 ) 3 The size is nanometer and has good dispersion and Re(CH 3 CO2 ) 3 Widely available sources. Use Re(CH 3 CO 2 ) 3 Can introduce Re 3+ Oleic acid and 1-octadecene are the reaction solvents, and the two act as surfactants to react with NaReF 4 The crystal growth size of the matrix plays a limiting role, preventing NaReF 4 The size gets bigger.
[0037] S2, stirring the first mixed solution and heating it to 140-170° C., preferably 150° C., and reacting for 30-50 min, preferably 40 min;
[0038] The above steps heat Re(CH 3 CO 2 ) 3 The solution, oleic acid and 1-octadecene react.
[0039] S3, adding citrate to the first mixed solution, mixing evenly to obtain a second mixed solution, heating the second mixed solution at 140-170° C., preferably 150° C., for 8 min-11 min, preferably 10 min, and then cooling to room temperature;
[0040] The citrate in this step provides the material for forming carbon dots, and the citrate and the first mixed solution can undergo a preliminary reaction at this temperature.
[0041] S4, adding NaOH methanol solution and NH4F methanol solution to the second mixed solution at room temperature, heating the second mixed solution to 40-60° C., preferably 50° C., and reacting for 25 min-40 min, preferably 30 min, to obtain a third mixed solution;
[0042] The addition of NaOH methanol solution is mainly to introduce Na ions, NH 4 F methanol solution is added with F ions and Re(CH 3 CO 2 ) 3 The solution then forms NaReF 4 .
[0043] S5, heating the third mixed solution to 90-110° C., preferably 90-110° C., and evacuating the solution, then heating the third mixed solution to 280-320° C., preferably 290° C., and reacting the solution under a nitrogen atmosphere for 1-3 h, preferably 2.5 h, and naturally cooling the third mixed solution to room temperature;
[0044] Under high temperature reaction, the carbon dots formed by citrate can be embedded into NaReF 4 middle.
[0045] S6, adding the ethanol solution and the cyclohexane solution to the third mixed solution, mixing them evenly to obtain a fourth mixed solution, and then centrifuging the fourth mixed solution to obtain the precipitated hyd-CDs@NaReF 4 Nanoparticles, hyd-CDs@NaReF sedimentation 4 The nanoparticles are washed;
[0046] The ethanol solution was added mainly to allow hyd-CDs@NaReF 4 The nanoparticles are precipitated so that they can be separated from the solvent by centrifugation later; the addition of cyclohexane solution is mainly to remove oleic acid and 1-octadecene that have not participated in the reaction.
[0047] S7, then wash hyd-CDs@NaReF with ethanol solution 4 Nanoparticles, then hydrochloric acid solution hyd-CDs@NaReF 4 Nanoparticles were acid-washed to remove hyd-CDs@NaReF 4 The hydrophobic groups of the nanoparticles were removed to obtain water-soluble hyd-CDs@NaReF4 composite materials which were redispersed in aqueous solution.
[0048] hyd-CDs@NaReF obtained in step S6 4 NaReF in Nanoparticles 4 Oleic acid-terminated NaReF 4 The benchmark, so the hyd-CDs@NaReF obtained in step S6 4 The surface of the nanoparticles is rich in hydrophobic oleic acid ligands, so step S7 is to use hydrochloric acid to treat the hyd-CDs@NaReF in step S6. 4 The nanoparticles were acid washed to make hyd-CDs@NaReF 4 There is no ligand on the surface of the nanoparticles, so the hyd-CDs@NaReF 4 There is no hydrophobic group on the surface of the nanoparticles. The hyd-CDs@NaReF obtained after step S7 4 The nanoparticles are hydrophilic hyd-CDs@NaReF 4 Nanoparticles. At the same time, hyd-CDs@NaReF 4 NaReF in Nanoparticles 4 Therefore, the hyd-CDs@NaReF obtained in step S7 4 Nanoparticles based on NaReF 4The size of hyd-CDs@NaReF in step S7 can be realized in nanometer scale. 4 There is no ligand on the surface and no aggregation occurs, so it can be well dispersed in aqueous solution. In addition, the hyd-CDs@NaReF obtained in step S7 4 NaReF in Nanoparticles 4 The acid-resistant matrix is an acid-resistant matrix and can be well dispersed in strong acid solutions, which expands the NaReF 4 Application scenarios of nanoparticles.
[0049] In this embodiment, in S1, each mole of Re(CH 3 CO 2 ) 3 The solution is added with 5min~8ml of oleic acid and 15min~20ml of 1-octadecene, preferably 6ml of oleic acid, preferably 16ml of 1-octadecene.
[0050] In this embodiment, in S2, a galvanic temperature sensor is added to the first mixed solution, and stirring is performed using a stirring magnet.
[0051] In this embodiment, in S3, each mole of Re(CH 3 CO 2 ) 3 50 mg to 100 mg of citrate is added to the solution, preferably 60 mg of citrate.
[0052] In this embodiment, in S4, each mole of Re(CH 3 CO 2 ) 3 The solution is added with 1.5 mmol to 3 mmol of NaOH methanol solution, preferably 1.5 mmol to 3 mmol, and 2 mmol to 5 mmol of NH 4 F methanol solution, preferably 3 mmol.
[0053] In this embodiment, in S5, the step of vacuum treatment includes: using a vacuum pump, connecting the vacuum pump to a double-row tube, inserting the double-row tube into the third mixed solution for degassing for 8 minutes to 12 minutes, preferably 10 minutes.
[0054] In this embodiment, in S6, each mole of Re(CH 3 CO 2 ) 3 The solution is added with 15ml-25ml of ethanol solution, preferably 15ml-25ml, and 10ml of cyclohexane solution, preferably 10ml.
[0055] In this embodiment, in S7, each mole of Re(CH 3 CO2 ) 3 The solution is washed with 10 ml to 25 ml of ethanol solution, preferably 20 ml, per mole of Re (CH 3 CO 2 ) 3 The solution uses 4 ml to 8 ml of hydrochloric acid solution, preferably 6 ml of hydrochloric acid solution.
[0056] In this embodiment, the concentration of the hydrochloric acid solution is 1 mol / L to 2 mol / L, preferably 1.5 mol / L, and the number of acid washings is 2 to 3.
[0057] The water-soluble carbon dot-based afterglow luminescent material is prepared according to the preparation method of the water-soluble carbon dot-based afterglow luminescent material.
[0058] Test Example 1
[0059] To further illustrate the performance of the material obtained by the method of the present invention, the following test example 1 is carried out: specifically comprising the following steps:
[0060] (1) 0.4 mmol of Re(CH 3 CO 2 ) 3 The solution, 3 ml of oleic acid and 7 ml of 1-octadecene were added into a two-necked round-bottom flask respectively.
[0061] (2) A thermocouple temperature sensor was installed in the flask, and a high temperature resistant stirring magnet was added. The mixed solution was heated to 160° C. under stirring and reacted at 160° C. for 40 minutes.
[0062] (3) Add 20-40 mg of citrate to the flask, continue heating the mixture at 160°C for 10 min, then remove the heating device and cool naturally to room temperature.
[0063] (4) At room temperature, 1 mmol of NaOH methanol solution and 1.6 mmol of NH 4 F methanol solution is added into the above two-necked flask.
[0064] (5) The temperature of the mixed solution was raised to 50°C and reacted at this temperature for 30 minutes.
[0065] (6) The temperature of the mixed solution was raised to 100° C. and degassed under vacuum conditions for 10 min using a vacuum pump and a double row tube to remove methanol and oxygen.
[0066] (7) Finally, the mixed solution was heated to 280-320°C and reacted under a nitrogen atmosphere for 1-3 hours.
[0067] (8) Remove the heating device and allow the mixed solution in the flask to cool naturally to room temperature.
[0068] (9) Add 8 ml of ethanol solution and 4 ml of cyclohexane solution to the flask, then transfer the mixed solution in the flask to a 50 ml centrifuge tube and centrifuge (8000-12000 rpm, 3-10 min) to obtain the precipitated hyd-CDs@NaReF 4 Nanoparticles.
[0069] (10) Wash the mixture twice more with 8 ml of ethanol solution and 4 ml of cyclohexane solution.
[0070] (11) Then, the obtained water-soluble hyd-CDs@NaReF was treated with acid and washed three times with 8 ml of ethanol solution and 2 ml of dilute hydrochloric acid solution (2 mol / L). 4 The composite material was redispersed in aqueous solution.
[0071] Performance Testing:
[0072] The performance test of the hyd-CDs@NaYF4 composite material obtained in Experimental Example 1 was carried out, and the following results were obtained:
[0073] Figure 1 The hyd-CDs@NaYF synthesized in Experimental Example 1 4 Transmission electron microscope image of the composite material. From the image, we can see the size of the material, which is spherical. From the image, we can see that the particle size distribution of the composite material is uniform, and the particle size is about 50nm. It can be seen that the hyd-CDs@NaYF4 composite material can reach the nanoscale.
[0074] Figure 2 The hyd-CDs@NaYF synthesized in Experimental Example 1 4 The X-ray diffraction pattern of the composite material corresponds one to one with the standard diffraction peaks of the pure hexagonal phase, indicating that the synthesized composite material is a pure hexagonal phase.
[0075] Figure 3 The hyd-CDs@NaYF synthesized in Experimental Example 1 4 The fluorescence spectra and afterglow excitation / emission spectra of the composite material dispersed in aqueous solution were measured at different excitation wavelengths, as well as the afterglow lifetime decay curve measured at 365nm excitation and 522nm emission. 4The maximum fluorescence emission peak of hyd-CDs@NaYF is located at about 470nm; the afterglow emission spectra under different excitation wavelengths show that the composite material has a double-peak emission, which is approximately located near 470nm and 520nm; the afterglow lifetime decay curve excited at 360nm is fitted by three exponentials, and the afterglow lifetime of the composite material is 596ms. 4 The composite material has a stable afterglow luminescence lifetime.
[0076] Figure 4 Experimental Example 1 Synthesis of hyd-CDs@NaYF 4 The composite material was dispersed in water, hydrochloric acid (38%) and nitric acid (68%) and ultrasonically treated for 30 minutes. The sample photos were taken after the fluorescent lamp and 365nm ultraviolet lamp were turned on and off. After the ultraviolet lamp was turned off, an obvious afterglow phenomenon was observed, indicating that the composite material has good stability in strong acid solutions and can be used in some harsh special environments.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a water-soluble carbon dot-based afterglow luminescent material, characterized in that: The following steps are involved: S1, respectively add Re(CH3CO2)3 solution, oleic acid and 1-octadecene into a container, mix well, and obtain a first mixed solution, S2, stirring the first mixed solution and heating it to 140° C. to 170° C., reacting for 30 min to 50 min; S3, adding citrate to the first mixed solution, mixing evenly to obtain a second mixed solution, heating the second mixed solution at 140° C. to 170° C. for 8 min to 11 min, and then cooling to room temperature; S4, adding NaOH methanol solution and NH4F methanol solution to the second mixed solution at room temperature, heating the second mixed solution to 40° C. to 60° C., and reacting for 25 min to 40 min to obtain a third mixed solution; S5, heating the third mixed solution to 90° C. to 110° C., evacuating the solution, then heating the third mixed solution to 280° C. to 320° C., reacting the solution under a nitrogen atmosphere for 1 h to 3 h, and naturally cooling the third mixed solution to room temperature; S6, adding ethanol solution and cyclohexane solution to the third mixed solution, mixing evenly to obtain a fourth mixed solution, and then centrifuging the fourth mixed solution to obtain precipitated CDs@NaReF4 nanoparticles, and washing the precipitated CDs@NaReF4 nanoparticles with a mixed solution of ethanol solution and cyclohexane solution; S7, then wash the CDs@NaReF4 nanoparticles with an ethanol solution, and then use a hydrochloric acid solution to wash the CDs@NaReF4 nanoparticles to remove the hydrophobic groups of the CDs@NaReF4 nanoparticles to obtain a water-soluble hyd-CDs@NaReF4 composite material.
2. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 1, characterized in that: In S1, 5 ml to 8 ml of oleic acid and 15 ml to 20 ml of 1-octadecene are added per mole of Re(CH3CO2)3 solution.
3. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 2, characterized in that: In S2, a galvanic temperature sensor is added to the first mixed solution, and stirring is performed using a stirring magnet.
4. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 3, characterized in that: In S3, 50 mg to 100 mg of citrate is added per mole of Re(CH3CO2)3 solution.
5. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 1, characterized in that: In S4, 1.5 mmol to 3 mmol of NaOH methanol solution and 2 mmol to 5 mmol of NH4F methanol solution are added per mole of Re(CH3CO2)3 solution.
6. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 1, characterized in that: In S5, the step of vacuum treatment includes: using a vacuum pump, connecting the vacuum pump to a double-row tube, and inserting the double-row tube into the third mixed solution for degassing for 8 minutes to 12 minutes.
7. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 1, characterized in that: In S6, 15 ml to 25 ml of ethanol solution and 5 ml to 15 ml of cyclohexane solution are added per mole of Re(CH3CO2)3 solution.
8. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 1, characterized in that: In S7, 10 ml to 25 ml of ethanol solution is used for each mol of Re(CH3CO2)3 solution for washing, and 4 ml to 8 ml of hydrochloric acid solution is used for each mol of Re(CH3CO2)3 solution for washing.
9. The method for preparing the water-soluble carbon dot-based afterglow luminescent material according to claim 8, characterized in that: The concentration of the hydrochloric acid solution is 1 mol / L to 2 mol / L, and the number of acid washing times is 2 to 3.
10. A water-soluble carbon dot-based afterglow luminescent material, characterized in that: The material is prepared by the method for preparing the water-soluble carbon dot-based afterglow luminescent material according to any one of claims 1 to 9.
Citation Information
Patent Citations
NaYF4 and carbon dot nano composite material and preparation method and applications thereof
CN108893102A
Carbon dot-based room-temperature phosphorescent composite material capable of stably emitting afterglow as well as preparation method, application and use method thereof
CN113913186A
NaYF4: Yb, Er and carbon dot nanocomposite and preparation method thereof
CN115058242A
Preparation method of rare earth doped Cs2NaYF6 long-afterglow nano luminescent material
CN118325610A
Red light afterglow carbon dot material as well as preparation method and application thereof
CN118853154A